2015
DOI: 10.1111/imm.12483
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous interleukin‐33 targets myeloid‐derived suppressor cells and generates periphery‐induced Foxp3+ regulatory T cells in skin‐transplanted mice

Abstract: SummaryInterleukin-33 (IL-33) has been a focus of study because of its variety of functions shaping CD4 + T-cell biology. In the present work, we evaluated the modulatory effect of IL-33 on suppressor cells in an in vivo transplantation model. C57BL/6 wild-type mice were grafted with syngeneic or allogeneic skin transplants and treated with exogenous IL-33 daily. After 10 days of treatment, we analysed draining lymph node cellularity and found in allogeneic animals an increment in myeloid-derived suppressor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 31 publications
4
30
1
Order By: Relevance
“…We hypothesized that the strong anti-inflammatory effect of IL-33 in CIA is in part mediated through Treg expansion and activation. Indeed, our work shows that IL-33 administration in vivo increases the frequency of Tregs, confirming in vitro and in vivo data obtained in three other studies performed in Con Ainduced hepatitis (46) and in allograft models (13,14). It was also shown that IL-33 is a key regulator of intestinal immune response by promoting Tregs in the intestine (47).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We hypothesized that the strong anti-inflammatory effect of IL-33 in CIA is in part mediated through Treg expansion and activation. Indeed, our work shows that IL-33 administration in vivo increases the frequency of Tregs, confirming in vitro and in vivo data obtained in three other studies performed in Con Ainduced hepatitis (46) and in allograft models (13,14). It was also shown that IL-33 is a key regulator of intestinal immune response by promoting Tregs in the intestine (47).…”
Section: Discussionsupporting
confidence: 90%
“…However, a similar amplification of this type 2 immune response, initiated by IL-33, aggravates asthma, which is clearly a Th2-driven disease (12). Moreover, it has recently been shown that IL-33 can activate and promote CD4 + Foxp3 + regulatory T cell (Treg) expansion, thus protecting mice from cardiac or skin transplant rejection (13,14). In this study, we investigated the role of IL-33 in a model of chronic inflammatory arthritis.…”
mentioning
confidence: 99%
“…In this context, it was demonstrated that IL-33 could also expand MDSCs, which in turn generate periphery-induced Foxp3 + Treg cells mediating cardiac and skin allograft survival1852. Moreover, it was reported that an MyD88-dependent MDSC population that express IL-10 expanded after CLP in mice, contributing to the T cell suppression seen after sepsis53.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough is the fact that RA is involved in Th1, Th2, Th17 and Treg differentiation, affecting a plethora of immunological events. On the other hand, IL-33 has been recently reported as an inducer of Treg cells as well (in vitro and in vivo), adding to the previous data stating that IL-33 may drive either Th1 or Th2 responses [12].…”
Section: Discussionmentioning
confidence: 77%